Rwanda : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper presents a Joint Staff Advisory Note of Rwanda's Poverty Reduction Strategy Paper (PRSP) Annual Progress Report. To enhance transparency and accountability, planning and budgeting processes necessary for the monitoring of the PRSP have improved, an organic budget law has been submitted to Parliament, and an action plan to create a modern public financial management system has been adopted. The demobilization effort has advanced and strategies in the social sectors have been very successful. Efficient transportation links, both domestic and international, are crucial for improving commerce and diversifying the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet